Experimental Research on Thermomechanical Properties of Thermal Energy Storage Cement Mortar Incorporated with Phase-Change Material - Kunyang Yu; Yong Huang; Bo Jin; Yushi Liu (Advances in Civil Engineering)
In the current work, the thermal energy storage cement mortars were prepared by physical mixing between cement mortar and form-stable hydrated salt based on disodium hydrogen phosphate dodecahydrate/carbon nanofiber-expanded graphite (DSP/CNF-EG). The DSP/CNF-EG was incorporated into cement mortar through replacing standard sand of 5 wt%, 10 wt%, and 15 wt%. The pore structure results obtained from the mercury intrusion porosimeter (MIP) demonstrated that the incorporation of DSP/CNF-EG form-stable hydrated salt PCM can cause the increased porosity of the cement mortar. The mechanical strengths of the thermal energy storage cement mortars were decreased with increasing DSP/CNF-EG incorporation amount, and they still meet the strengths of the building envelope. Moreover, dynamic mechanical analysis (DMA) results suggested that the damping properties of the thermal energy storage cement mortar were enhanced by incorporating DSP/CNF-EG, which were related to the porosity and the internal friction action. In addition, the thermal conductivity and the specific heat capacity results confirmed that the introduction of DSP/CNF-EG can endow cement mortar with excellent thermal energy storage capacity. The thermal performance test further indicated that the thermal energy storage cement mortar showed good endothermic and exothermic characteristics, and it played a prominent role in weakening the indoor temperature peak.